Investigation on diesel spray flame evolution and its conceptual model for large nozzle and high-density of ambient gas. (1st May 2023) - Liu, Long; Fu, Shiyi; Han, Changfu
Highlights: A conceptual model for large nozzle spray and flame evolution. The reason of ignition position at the mid-part of large nozzle spray. Air drag affects large nozzle spray periphery causes a wrinkle boundary of flame. High ambient gas density accelerates spray evaporation and flame enveloping. Swirl pushes the windward droplets to spray tip and changes the ignition position. Abstract: To reveal the theory behind the ignition phenomenon of large nozzle diameter spray and better organize the combustion of two-stroke marine diesel engine, in this article, the numerical simulation has been made by CONVERGE to study the developing process of large nozzle spray and flame in constant volume combustion chamber. Spray and flame characteristics for different nozzle diameters 0.5 mm, 0.625 mm and 0.875 mm are compared to investigate the effect of nozzle diameter on spray and flame characteristics. Then the ambient pressure is increased and a swirl is added to discuss the spray and flame characteristics under high-density of ambient gas and swirl. It was shown that for large nozzle led spray heads, there would be several stripping processes of the spray head periphery under air-dragging work. The first stripped fuel remains on the periphery of the spray upstream, evaporating and igniting. The flame propagates through the stripped fuel evaporation path from the ignition position to the spray tip. Flame propagation stops after nearly reaching the spray tip due to the lack of the combustible mixture but the presence of unevaporated liquid fuel, which was caused by the large nozzle diameter slowing down the spray tip evaporation. The liquid fuel at the spray tip then evaporates and mixes with the air. Then flame begins to propagate through the vapor fuel path, enveloping the entire spray. Increasing ambient pressure accelerates spray break-up and evaporation. The flame can directly envelop the spray through the combustible mixture in the spray tip. Adding swirl pushes the separated swirl-facing side-periphery fuel to the spray tip. Ignition occurs in the spray tip and mid-part of spray leeside then flame propagates in the direction of each other direction.